2012
DOI: 10.1111/j.1468-1331.2012.03834.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing blood pigment analysis in cerebrospinal fluid for the diagnosis of subarachnoid haemorrhage – a practical approach

Abstract: Our data show that a raised bilirubin calculated using the Leiden method seems to have a lower specificity than the UK NEQAS guideline. For practical reasons, it seems advantageous to use the Leiden method as a screening method and use the UK NEQAS guideline if a positive result is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In our systematic review, subgroup analyses were performed to explore reasons for the heterogeneity in the results. In the two studies that used the UKNEQAS guidelines, their pooled sensitivity and specificity were 93% and 99%, respectively – much more accurate than visual inspection . The less than 100% sensitivity might be due to the fact that LP was not always performed 12 h or more after headache onset in one of these two studies .…”
Section: The Case Formentioning
confidence: 94%
See 4 more Smart Citations
“…In our systematic review, subgroup analyses were performed to explore reasons for the heterogeneity in the results. In the two studies that used the UKNEQAS guidelines, their pooled sensitivity and specificity were 93% and 99%, respectively – much more accurate than visual inspection . The less than 100% sensitivity might be due to the fact that LP was not always performed 12 h or more after headache onset in one of these two studies .…”
Section: The Case Formentioning
confidence: 94%
“…In the two studies that used the UKNEQAS guidelines, their pooled sensitivity and specificity were 93% and 99%, respectively -much more accurate than visual inspection. 18,19 The less than 100% sensitivity might be due to the fact that LP was not always performed 12 h or more after headache onset in one of these two studies. 19 Differences in spectrophotometry reported in the studies found for our systematic review included the use of xanthochromic index 8,20 and spectrophotometric scanning at discrete rather than continuous wavelengths.…”
Section: Kevin H Chumentioning
confidence: 97%
See 3 more Smart Citations